The research on local human development, participation and social policy (Mayéutica Revista Científica de Humanidades y Artes, 2013)
The proposal to consider the research line in Local Human Development, Participation and Social Policy, responds to the objective of strengthening investigative work, in a problematic area of ​​great relevance for Venezuelan society, as are the problems related to the development local human rights, territorial development, participation and politics Social. Research in this field, both of the teachers as of the students, can be addressed through research projects, field works, monographic reports individual or collective, and even with internships, what which constitutes a strength to sustain academic work. In addition, the establishment of cooperation agreements and the action of teachers and students in related activities with the alternatives of joint work between curricular units. All these activities open the possibility of incorporating to other institutions and people to this work.